2009
DOI: 10.1254/jphs.09183fp
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Disappearance of the Inhibitory Effect of Vascular Endothelium on Agonist-Induced Vasoconstriction in Rat Mesenteric Vascular Beds

Abstract: Abstract. We previously reported that endothelium-derived hyperpolarizing factor (EDHF)-mediated response time-dependently suppressed methoxamine-induced vasoconstriction in mesenteric vascular beds isolated from 8-week-old rats. We investigated age-related changes in endothelial regulation of methoxamine-induced vasoconstriction. Mesenteric vascular beds isolated from young (8-week-old) to adult (16-week-old) rats were perfused, and changes in perfusion pressure induced by continuous perfusion of methoxamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In the present study, the major findings are that exogenously applied acetylcholine and A23187 in the mouse perfused mesenteric vascular bed caused a concentrationdependent vasodilation, which is well consistent with the response in the rat perfused mesenteric vascular bed (13,14). Since responses to both acetylcholine and A23187 were abolished by endothelium dysfunction, they appear to be dependent on an intact endothelium, although the underlying signaling pathways differ between acetylcholine and A23187.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the present study, the major findings are that exogenously applied acetylcholine and A23187 in the mouse perfused mesenteric vascular bed caused a concentrationdependent vasodilation, which is well consistent with the response in the rat perfused mesenteric vascular bed (13,14). Since responses to both acetylcholine and A23187 were abolished by endothelium dysfunction, they appear to be dependent on an intact endothelium, although the underlying signaling pathways differ between acetylcholine and A23187.…”
Section: Discussionsupporting
confidence: 85%
“…1, A and B, an initial phase of methoxamine-induced vasoconstriction was augmented by endothelium dysfunction. A previous report has demonstrated that in rat mesenteric arteries, endothelium acts to depress methoxamine-induced vasoconstriction by releasing EDHF (14,24). Therefore, EDRF and/or EDHF in the endothelium of mouse mesenteric arteries is likely to suppress methoxamine-induced vasoconstrictions.…”
Section: A23187 (Nmol)mentioning
confidence: 90%
See 2 more Smart Citations
“…With other factors equal, an increase in SMC membrane area would require larger endothelium-derived ionic currents to evoke the same change in SMC membrane potential. The increased requirement for current flow in SMCs from the aged could produce attenuated endotheliumdependent hyperpolarization, contributing to the impaired endothelium-dependent dilation that accompanies aging (25,30). Increased SMC capacitance also would be expected to attenuate the transmission of electrical signals along the vessel and contribute to impairment of conducted (ascending) vasodilation of feed arteries (19).…”
Section: Discussionmentioning
confidence: 99%